8. Analisis Kepemimpinan Kemampuan Manajerial Kepala Madrasah dan Disiplin Kerja Guru Dalam Meningkatkan Kinerja Guru - Husnul Mu'amalah (Jurnal Dewantara, 2020)
Managerial capacity headmaster who qualified to participate in the building of teacher performance as steps an organization madrasas controlled by a school principal. In this studi, in South Lampung the results showed; 1) Leadership Principals run with its role as a leader, motivator, supervisors, educators and administrators can improve the performance of teachers. 2) Process management is performed by the headmaster in improving the performance of the teacher will not run properly without qualified managerial competence which is owned by the headmaster as manager at the school, as well as the support and solid cooperation between the head madrasah, teachers and other academic community. 3) Aspects of teachers' work discipline is known that there are many teachers who do not work well to do discipline. 4) Headmaster has been functioning with maximum leadership through the implementation of strict work discipline teachers and supported by good managerial ability so as to improve the performance of teachers.